Awareness of dementia risk factors among healthcare professionals at Hamad Medical Corporation, Qatar: a cross-sectional survey - Al Hamad, Hanadi; Sathian, Brijesh (Frontiers in Public Health, 2024)
Background Dementia, a degenerative neurological disorder, is estimated to affect 82 million people worldwide by 2030 and 152 million by 2050, with a sharp increase in its incidence in the Middle East and Qatar. Lifestyle factors, such as smoking, physical inactivity, and obesity, may account for up to 40% of dementia cases. Healthcare practitioners who play an important role in health promotion must understand the modifiable risk and protective factors for dementia. This study investigated healthcare professionals' knowledge of dementia risk factors at Hamad Medical Corporation in Qatar. Methods A sample of 737 healthcare professionals was recruited using simple random sampling from Hamad Medical Corporation. The target population included physicians, nurses, and allied healthcare workers from various departments. The participants completed an online survey between 1st January and December 31, 2023. The survey included questions on modifiable risk factors, preventive interventions, and dementia-related information sources. Results The study revealed that 76% of participants believed in dementia prevention and 87.4% were interested in learning about lifestyle choices and dementia risk. The majority of the participants were female and non-Qataris. Challenges to dementia risk reduction include lack of understanding, time restrictions, and motivational obstacles. Awareness of risk factors such as depression, alcohol use, and physical inactivity was identified. Digital platforms are the dominant source of information, highlighting the need for more dementia education and prevention programs. Conclusion Given the gaps identified in knowledge, we recommend further training to improve the knowledge of healthcare professionals. In addition, further exploration of patients and caregiverss is warranted.